Intumescent coating modelling based on small scale experimental tests - Mesquita, L.M.R. (2010)
An investigation of two different intumescent coatings used in steel fire protection has been performed to evaluate their efficiency. Among other quantities, the steel temperature and the intumescence thickness variation were measured. A mathematical model for the intumescent coating is developed. It considers the coating decomposition and models the protection by two layers, the reacted and the unreacted layer. A comparison between the experimental results and the ones obtained from the numerical model is presented.